Experimental Study of Enhancing Oil Recovery with Weak Base Alkaline/Surfactant/Polymer - Dandan Yin; Dongfeng Zhao; Jianfeng Gao; Jian Gai (International Journal of Polymer Science)
Na2CO3 was used together with surfactant and polymer to form the Alkaline/Surfactant/Polymer (ASP) flooding system. Interfacial tension (IFT) and emulsification of Dagang oil and chemical solutions were studied in the paper. The experiment results show that the ASP system can form super-low interfacial tension with crude oil and emulsified phase. The stability of the emulsion is enhanced by the Na2CO3, surfactant, and the soap generated at oil/water contact. Six core flooding experiments are conducted in order to investigate the influence of Na2CO3 concentration on oil recovery. The results show the maximum oil recovery can be obtained with 0.3 wt% surfactant, 0.6 wt% Na2CO3, and 2000 mg/L polymer. In a heterogeneous reservoir, the ASP flooding could not enhance the oil recovery by reducing IFT until it reaches the critical viscosity, which indicates expanding the sweep volume is the premise for reducing IFT to enhance oil recovery. Reducing or removing the alkali from ASP system to achieve high viscosity will reduce oil recovery because of the declination of oil displacement efficiency. Weak base ASP alkali can ensure that the whole system with sufficient viscosity can start the medium and low permeability layers and enhance oil recovery even if the IFT only reaches 10−2 mN/m.